Diagnostic delay of multiple sclerosis: prevalence, determinants and consequences - Uher, Tomas; Adzima, Adrian; Srpova, Barbora; Noskova, Libuse; Maréchal, Bénédicte; Maceski, Aleksandra Maleska; Krasensky, Jan; Stastna, Dominika; Andelova, Michaela; Novotna, Klara; Vodehnalova, Karolina; Motyl, Jiri; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2023)
BACKGROUND: Early diagnosis and treatment of patients with multiple sclerosis (MS) are associated with better outcomes; however, diagnostic delays remain a major problem. OBJECTIVE: Describe the prevalence, determinants and consequences of delayed diagnoses. METHODS: This single-centre ambispective study analysed 146 adult relapsing-remitting MS patients (2016-2021) for frequency and determinants of diagnostic delays and their associations with clinical, cognitive, imaging and biochemical measures. RESULTS: Diagnostic delays were identified in 77 patients (52.7%), including 42 (28.7%) physician-dependent cases and 35 (24.0%) patient-dependent cases. Diagnosis was delayed in 22 (15.1%) patients because of misdiagnosis by a neurologist. A longer diagnostic delay was associated with trends towards greater Expanded Disability Status Scale (EDSS) scores (B = 0.03; p = 0.034) and greater z-score of the blood neurofilament light chain (B = 0.35; p = 0.031) at the time of diagnosis. Compared with patients diagnosed at their first clinical relapse, patients with a history of >1 relapse at diagnosis (n = 63; 43.2%) had a trend towards greater EDSS scores (B = 0.06; p = 0.006) and number of total (B = 0.13; p = 0.040) and periventricular (B = 0.06; p = 0.039) brain lesions. CONCLUSION: Diagnostic delays in MS are common, often determined by early misdiagnosis and associated with greater disease burden.
Keywords: recidiva; misdiagnosis; Magnetic Resonance Imaging; mozek; magnetická rezonanční tomografie; Humans; Multiple Sclerosis; prevalence; dospělí; Delayed Diagnosis; lidé; magnetic resonance imaging; disability; Adult; brain lesion; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; roztroušená skleróza; multiple sclerosis; Brain; cerebrospinal fluid; Recurrence; opožděná diagnóza; Prevalence; neurofilament; Delayed diagnosis